Atomic-level understanding layer-by-layer formation process of TiCx on carbon film. (20th January 2021) - Liu, Jingchun; Jiang, Weiyan; Liu, Junxia; Long, Dewu; Wang, Jianqiang
Abstract: TiCx coating film was fabricated by a novel two-step deposition strategy in molten salts media, namely carbon film was prepared firstly on the substrate and then following transformation of C to TiCx by deposition of Ti on the C film. The latter step was achieved by electrochemical deposition of Ti in FLiNaK-K2 TiF6 -Ti, in which the Ti 2+ ion was the dominant species. It was found that the transformation of C to TiCx is a diffusion control process rather than deposition control one, implying that the interdiffusion between Ti and C phase is the decision step. To reveal the formation process, calculation simulation was further conducted. The results of first-principle calculation demonstrate that the deposited Ti atom prefers to combine to the central site of the graphite surface. Then, formation of Ti layer will take place as the atom number increased by continuous deposition. Subsequently, the interdiffusion between Ti and C phase motivated by repulsion, concentration gradient and Gibbs free energy will contribute to the transformation of composite. Such initial formation process of TiCx on the C film was further confirmed by the results of charge transfer between Ti and C atoms and its electronic state. The results of deposition and diffusion of Ti and C atoms manifest that the formation of TiCx is a reconstruction rather than atom diffusion process. Graphical abstract: Image, graphical abstract